2009
DOI: 10.3109/08860220903100713
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Genomics and Proteomics in Nephrology

Abstract: An increasing number of patients suffering from renal diseases and limitations in standard diagnostic and therapeutic approaches has created an intense interest in applying genomics and proteomics in the field of nephrology. Genomics has provided a vast amount of information, linking the gene activity with disease. However, proteomic technologies allow us to understand proteins and their modifications, elucidating properties of cellular behavior that may not be reflected in analysis of gene expression. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…The era of high-throughput techniques and personalized medicine has accelerated the discovery of fresh and promising therapeutic platforms [73]. Emerging anticancer strategies are based on the development of nanocarriers that can bind multiple drugs and molecules, which can selectively and efficiently target cancer cells, especially CSCs.…”
Section: Cancer Stem Cell-targeted Therapiesmentioning
confidence: 99%
“…The era of high-throughput techniques and personalized medicine has accelerated the discovery of fresh and promising therapeutic platforms [73]. Emerging anticancer strategies are based on the development of nanocarriers that can bind multiple drugs and molecules, which can selectively and efficiently target cancer cells, especially CSCs.…”
Section: Cancer Stem Cell-targeted Therapiesmentioning
confidence: 99%
“…Genomics and proteomics represent powerful and promising tools in unraveling complex molecular networks 41,42 . Investigators have attempted to understand the subset of proteins whose expression levels are directly altered by oxidants, or those proteins that are posttranslation-ally modified in a redox-dependent fashion 43 .…”
Section: Future Implicationsmentioning
confidence: 99%
“…Recent proteomics based study identified gold (III) porphyrin 1a as a new, potent anticancer drug that induces apoptosis through both caspase-dependent and caspase-independent mitochondrial pathways, and demonstrated that intracellular oxidation affected gold (III) porphyrin 1a-induced apoptosis 44 . The difficulty with advanced "omics" methodologies is how to translate the provided data into a meaningful clinical context, ie into clinical trial design and subsequently into routine clinical use 41 .…”
Section: Future Implicationsmentioning
confidence: 99%
“…Chronic disease processes and drug toxicities are characterized by silent and progressive courses and non-specific symptoms that, by current clinical diagnostic tools, often remain undetected in their early stages [47]. The quality of diagnostic tools is determined by their sensitivity and specificity.…”
Section: Molecular Marker Strategies- Why Are They Predictive?mentioning
confidence: 99%